Type 1 Corticotropin-Releasing Factor Receptor Expression Reported in BAC Transgenic Mice: Implications for Reconciling Ligand-Receptor Mismatch in the Central CRF System - Justice, Nicholas J. (2008)
In addition to its established role in initiating the endocrine arm of the stress response, corticotropin-releasing factor (CRF) can act in the brain to modulate neural pathways that effect coordinated physiological and behavioral adjustments to stress. Although CRF is expressed in a set of interconnected limbic and autonomic cell groups implicated as primary sites of stress-related peptide action, most of these are lacking or impoverished in CRF receptor (CRFR) expression. Understanding the distribution of functional receptor expression has been hindered by the low resolution of ligand binding approaches and the lack of specific antisera, which have supported immunolocalizations at odds with analyses at the mRNA level. We have generated a transgenic mouse that reports expression of the principal, or type 1, CRFR (CRFR1). This mouse expresses GFP in a cellular distribution that largely mimics that of CRFR1 mRNA and is extensively colocalized with it in individual neurons. GFP-labeled cells display indices of activation (Fos induction) in response to central CRF injection. At the cellular level, GFP labeling marks somatic and proximal dendritic morphology with high resolution, and is also localized to axonal projections of at least some labeled cell groups. This includes a presence in synaptic inputs to central autonomic structures such as the central amygdalar nucleus, which is implicated as a stress-related site of CRF action, but lacks cellular CRFR1 expression. These findings validate a new tool for pursuing the role of central CRFR signaling in stress adaptation, and suggest means by which the pervasive ligand-receptor mismatch in this system may be reconciled.